PP83 Economic Impact Of Missed Vaccinations On The Italian National Health System. (23rd December 2022) - Di Brino, Eugenio; Basile, Michele; Rumi, Filippo; Cicchetti, Americo; ,
Abstract : Introduction: To provide a complete picture of the economic impact of the coronavirus disease 2019 (COVID-19) emergency for the Italian National Health System (NHS), an estimate was made of the costs to the NHS of vaccination hesitation. The concept of economic impact was investigated with reference to the volume of hospitalizations and days of intensive care required for patients with COVID-19 related to missed vaccinations, considering a vaccine efficacy of less than 100 percent. Methods: Data from the Istituto Superiore di Sanità were analyzed with respect to the number of people vaccinated in the general population, and the number of people with severe acute respiratory syndrome coronavirus 2 infection who were hospitalized or died in a one-month period stratified by vaccination status. The costs for unvaccinated patients admitted to a general hospital ward (Medical Area) or the intensive care unit were calculated. Results: Based on the number of preventable hospitalizations among unvaccinated people, the economic impact of missed vaccinations on the NHS in the 30-day period from 13 August 2021 to 12 September 2021 was estimated. Among the unvaccinated hospitalized patients, 5, 932 would have avoided hospitalization in the Medical Area and 715 would have avoided admission to the intensive care unit. Thus, each unvaccinated hospitalized patient had an average per capita cost of EUR 17, 408. The total costs amounted to EUR 69, 894, 715, comprising EUR 51, 166, 079 for hospitalizations in the Medical Area and EUR 18, 728, 636 for hospitalizations in intensive care. Conclusions: By evaluating the weekly incidence of hospitalizations per 100, 000 people stratified by vaccination status (unvaccinated, partially vaccinated, and fully vaccinated), it is possible to see that we are facing two distinct pandemics running together.